The need for psychological counseling in breast cancer patients before radiotherapy during the COVID-19 pandemic - Mo, Yan-Lin; Lai, Xiao-Ying; Mo, Min-Feng; Li, Ling; Zhu, Xiao-Dong (Frontiers in Psychology, 2022)
The aims of this study were to explore the need for psychological counseling in breast cancer patients before radiotherapy during the COVID-19 pandemic, to distinguish which type of psychological guidance they demanded and to investigate the related factors that could be associated with the need for psychological counseling. A total of 112 eligible patients diagnosed with stage I to IV breast cancer who had received surgery were included. The self-rating depression scale (SDS), self-rating anxiety scale (SAS), Pittsburgh sleep quality index (PSQI), cancer fatigue scale (CFS), and survey for the need for psychological counseling were completed for all subjects prior to radiotherapy. A total of 8.9% and 3.6% of patients suffered from depression and anxiety during the COVID-19 pandemic, respectively. The prevalence of sleep disturbance was 62.5%. Only 12.5% of the patients needed psychological counseling, especially for the type of tumor diagnosis and treatment rather than COVID-19-related protection. The higher the total CFS score was, the lower the need for psychological counseling in breast cancer patients during this pandemic (OR=0.91, 95% CI=0.84–0.98). Patients who received 7-8 chemotherapeutic cycles had 6.7 times the risk of needing psychological counseling when compared with those who received 1-6 chemotherapeutic cycles. Fewer breast cancer patients suffered from depression and anxiety before radiotherapy during the COVID-19 pandemic. However, a large number of patients complained of sleep disturbance and fatigue. The majority of patients did not need psychological counseling. More chemotherapeutic cycles or less fatigue could increase their risk of needing psychological counseling, especially for tumor diagnosis and treatment, but not COVID-19-related protection.